ANALISIS KINERJA LALU LINTAS JALAN URIP SUMOHARJO YOGYAKARTA - Anton Susanto; Zebta Bernad Siahaan; Bagus Hario Setiadji; Supriyono Supriyono (Jurnal Karya Teknik Sipil, 2014)
Yogyakarta city in ones of the big city in java, that straregic because of tourism and student city. The every years vehicle to in Yogyakarta be increase. There is be the main of jamming trafgic, ones of them is Urip Sumoharjo street from STA 03+100 – STA 03+585. From a sekunder data from dirjen Bina Marga Yogyakarta show of digit traffic growth daily being increase for 4 last year. The number of street ministry feasibility show with degree of saturation (DS), with condition DS < 0,75. The result of the analysis from survey on September 2013 show DS to existing road not eliginle with grades DS 1,25 because park ib roads so width then effectife traffic decreased of road capacity. Main of step solution jamming traffic are park optimalitation, with manage parking patters with some simulation in cornerand length with the reduction of parking on-street along 240 m of the junction the Galeria Mall, to meet the needs of the SRP which is less need to create a new SRP for making buildings with parking in the surrounding streets Urip Sumoharjo. After then steep feel not optimal to change of DS for the next 4 years, make a building parking in arround of Urip Sumoharjo. With it capacity of road will be increase so DS what quality last a long time same with increase of growth LHR Yogyakarta city in next year.